Synthesis of TiO2 with Hierarchical Porosity for the Photooxidation of Propene - Javier Fernández-Catalá; Laura Cano-Casanova; María Ángeles Lillo-Ródenas; Ángel Berenguer-Murcia; Diego Cazorla-Amorós (Molecules, 2017)
The elimination of volatile organic compounds (VOCs) at low concentration is a subject of great interest because these compounds are very harmful for the environment and human health. In this work, we have developed a synthesis methodology of TiO2 that allows obtaining meso-macroporous materials with hierarchical porosity and with high thermal stability for their application as photocatalysts in the removal of VOCs, specifically propene. The materials synthesized in this work were characterized by Scanning electron microscope (SEM), Transmission electron microscopy (TEM), powder X-ray diffraction (XRD), Thermogravimetric Analysis (TG), and nitrogen adsorption. It is observed that the samples calcined at 250 °C and 500 °C present a high photoactivity for the photooxidation of propene, which is similar to the benchmark material P25 (commercial TiO2). Moreover, the textural properties are better than those for P25, indicating that the samples are interesting for the preparation of photocatalysts with different conformations, such as in the form of coatings and fillings in different size scales.